Generation Z Work Readiness in the Digital Era: An Empirical Diagnosis and Conceptual HRM Collaboration Model at IAIN Parepare - Musmulyadi; Akilah, Fahmiah; Safrida (Ilomata International Journal of Management, 2026)
This study examines the work readiness of Generation Z students in the digital era within the institutional context of IAIN Parepare, Indonesia. Rapid technological change has increased the demand for graduates who possess both digital competencies and adaptive professional skills. However, higher education institutions often face challenges in aligning graduate competencies with evolving industry expectations. Using an exploratory sequential mixed-method design, this study first conducted qualitative interviews and focus group discussions with institutional leaders, lecturers, industry practitioners, and human resource professionals to explore existing competency gaps and institutional practices. Insights from this phase informed the development of a survey instrument administered to 50 respondents in the quantitative stage. Qualitative data were analyzed using thematic analysis, while quantitative data were examined through descriptive statistics, regression analysis, and structural equation modelling. The findings indicate that students demonstrate relatively strong soft skills such as communication, teamwork, and professional ethics, but show moderate readiness in several digital hard-skills areas, particularly technological proficiency and independent problem solving. Based on these empirical insights, the study proposed an applied conceptual model that integrates human resource management practices, pentahelix collaboration, and Islamic value integration as institutional strategies for strengthening graduate work readiness. Rather than presenting a university-validated framework, the model is intended as a context-specific conceptual proposal grounded in the empirical case of an Islamic higher education institution.